600 jaar Norbertijnen in Simpelveld - Horbach, M.J. (De Bongard: Tijdschrift van de Heemkundevereniging Simpelveld-Bocholtz, 1990)
Keywords: simpelveld

The 'White Canons' Rediscovered: clearance work at Tupholme Abbey - Bainbridge, Norman (History Today, 1990)
Norman Bainbridge on springtime for Tupholme Abbey.
Keywords: tupholme

Corhampton Church, Hampshire in the diocese of Portsmouth: the NADFAS record of church furnishings 1990 (Record of church furnishings, 1990)
Keywords: corhampton

Louka. 800 let premonstrátského kláštera Louka u Znojma na Morave (Cesta, 1990)
[800 Jahre des Prämonstratenserstiftes Klosterbruck bei Znaim in Mähren]
Keywords: louka

Lübsee (Ortsteil von Menzendorf): Dorfkirche - Baier, Gerd; Trost, Heinrich (Die Bau- und Kunstdenkmale in der mecklenburgischen Küstenregion, 1990)
Keywords: lübsee

Ein Streit im Kloster Pöhlde - Barke, Heinrich (Heimatblätter für den südwestlichen Harzrand, 1990)
Keywords: pöhlde

Regestenboek van het archief van de Abdij van Berne, 1400-1500: met inleiding en indices - Bavel, Huub van (Abdij van Berne, 1990)
Keywords: berne

800 Jahre Stift Klosterbruck - Bornemann, Hellmut (Verlag des Südmährischen Landschaftsrates, 1990)
Keywords: louka

Recherches sur l'abbaye de Saint-Augustin de Thérouanne (ordre de Prémontré) - Boussemart-Goze, Charlotte (Université de Lille III, 1990)
Keywords: saint-augustin-lès-thérouanne

Sumptuous arts at the Royal Abbeys in Reims and Braine : ornatus elegantiae, varietate stupendes - Caviness, Madeline Harrison (Princeton University Press, 1990)
Keywords: braine

Canonia lucensis. Počátky a prvních sto let života - Charouz, Jindřich Zdeněk (Ročenka Okresního archivu ve Znojmě, 1990)
Keywords: louka

Het klooster Cusemer - Colpa, Joan (Groninger Volksalmanak, 1990)
Keywords: kuzemer

Die heilige Elisabeth brachte barfuss ihre Tochter Gertrudis von Marburg zum Altenberg: vor 8 Jh. entstand das Kloster - Cornelius, Werner (Heimat an Lahn und Dill, 1990)
Keywords: altenberg

Zur Deutung umstrittener Urkunden des Klosters Broda - Deppe, Hans-Joachim (Carolinum : historisch-literarische Zeitschrift, 1990)
Keywords: broda

L'existence chimérique de l'abbé Henri II de Tongerlo (1207/1209) - Dijck, Leo Cyriel van (Analecta Praemonstratensia, 1990)
Keywords: tongerlo

Nochmals über die Beziehungen zwischen Speinshart und Tepl im späten Mittelalter - Dolista, Karel (Analecta Praemonstratensia, 1990)
Keywords: speinshart; teplá

Premonstratský klašter Milevsko - Dolista, Karel (Děkanský úřad, 1990)
[Das Prämonstratenserstift Mühlhausen]
Keywords: milevsko

Dale Abbey: the south range excavations and survey, 1985-87 - Drage, Christopher (The Derbyshire Archaeological Journal, 1990)
Keywords: dale

Charakterystyka stratyfikacji kulturowej wzgórza klasztornego w Strzelnie (woj: bydgoskie) - Dubikajtis, Jerzy; Sulkowska, Grażyna K.; Dubikajtis, Jolanta (Z badań nad średniowieczną architekturą Kujaw i Wielkopolski wschodniej, 1990)
Description of the culture stratification of the monastery hill in Strzelno (Bydgoszcz voivodship)
Keywords: strzelno

Nacimiento apogeo y decadencia de un monasterio castellano: Santa María de Aguilar de Campoo, siglos XII-XV - González de Fauve, María Estela (Codex Aquilarensis: Revista de arte medieval, 1990)
Keywords: aguilar de campoo

Inleiding tot de Vita Norberti B - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1990)
Keywords: 👤 norbert of xanten

Norbert en de oudste organisatie van de premonstratenzerorde - Grauwen, Wilfried Marcel (Analecta Praemonstratensia, 1990)
Keywords: 👤 norbert of xanten

Das Reichsstift Roggenburg 1126-1803. Geschichte, Kunst, Kultur - Gritzmann, Elisabeth (Landkreis Neu-Ulm, 1990)
Keywords: roggenburg

Apuntes sobre las tallas vegetales protogóticas en el monasterio de Sta. María la Real de Aguilar de Campóo - Hernando Garrido, José Luis (Actas del II congreso de historia de Palencia: Palencia en la historia de la lengua y literatura, 1990)
Keywords: aguilar de campoo

The White Canons, Abbeytown, Cill-na-Manach, 1260-1990. A History of the Monastery of the White Canons and Other Historical Places in the District of Maigh Seola - Higgins, Jim; McHugh, Anna (Crow's Rock Press, 1990)
Keywords: killamanagh

Das Kloster der Prämonstratenserinnen zu Ellen, 1190-1802 - Horstkötter, Ludger (Festausschuss "800 Jahre Dorf und Kloster Ellen", 1990)
Keywords: ellen

De stichtingsoorkonden van de abdij van Averbode (1133-1139), gevolgd door enkele verdachte oorkonden uit de twaalfde eeuw - Janssens, Herman (Analecta Praemonstratensia, 1990)
Keywords: averbode

Jan Želivský - Kopicková, Božena (Odkazy pokrokových osobností naší minulosti, 1990)
Keywords: 👤 jan želivský

Das Prämonstratenserstift Arnstein a. d. Lahn im Mittelalter (1139-1527) - Krings, Bruno (Veröffentlichungen der Historischen Kommission für Nassau, 1990)
Keywords: arnstein

Trzynastowieczne dokumenty premonstratensek w Żukowie w dyplomatariuszu przeora kartuskiego Jerzego Schwengla - Labuda, Gerard (Acta Universitatis Nicolai Copernici. Historia, 1990)
Keywords: żukowo

Le cartulaire de Valpriez, 1135-1250 - Lalanne, J.-M. (Editions du C.T.H.S., 1990)
Keywords: valpriez

Anciennes abbayes prémontrés landaises - Lalanne, V. (Voix de Belloc, 1990)
Keywords: 🇫🇷 france (general)

Ein Dachwerk des 13. Jahrhunderts: die Bekrönung des nördlichen Chorflankenturmes der Marienkirche in Gelnhausen - Ludwig, Thomas (Denkmalpflege in Hessen, 1990)
Keywords: gelnhausen (marienkirche)

Als Prämonstratenserkloster gegründet. 850 Jahre Arnstein an der Lahn - Luh, Hans Kurt (Hessische Heimat (Gießen), 1990)
Keywords: arnstein

Bischof Ludolf von Ratzeburg und die Neueinweihung der Bartholomäus-Kirche in Frankfurt am Main - Marx, Siegfried (s.n., 1990)
Keywords: 👤 ludolf of ratzeburg

Le grand passionaire enluminé de Weissenau et son scriptorium autour de 1200 - Michon, Solange (Slatkine, 1990)
Keywords: weissenau

Das "Opusculum compendiosum" des Wiltener Chorherren Michael Ausse, eine bisher nicht beachtete Darstellung der Gründungsgeschichte des Prämonstratenserordens - Neuhauser, Walter (Analecta Praemonstratensia, 1990)
Keywords: wilten

Das Stift Geras und die Grafen von Hardegg - Pfiffig, Ambros Josef (Geraser Hefte, 1990)
Keywords: geras

The origins of the Polish Premonstratensian Circary - Rajman, Jerzy (Analecta Praemonstratensia, 1990)
Keywords: 🇵🇱 poland (general)

Die Stiftsbibliothek Schäftlarn - Ruf, Martin (Bibliotheksforum Bayern, 1990)
Keywords: schäftlarn

"Specula strahoviensis." A proposito del collezionismo di curiosità in Boemia alla luce dell'esempio praghese di Strahov e di altri conventi contemporanei - Sanvito, Paolo (Schifanoia. Notizie dell'Istituto di Studi Rinascimentali di Ferrara, 1990)
Keywords: strahov

Bauarchäologische Forschungen in der Klausur des Prämonstratenserstiftes Jerichow - Schmitt, Reinhard (Die mittelalterliche Plastik in der Mark Brandenburg : Protokollband des internationalen Kolloquiums vom 2. bis 4. März 1989 in den Staatlichen Museen zu Berlin, Bodemuseum, 1990)
Keywords: jerichow

Baugeschichtliche Untersuchungen in der Klausur des Klosters Jerichow. Tl. 2 - Schmitt, Reinhard (Magdeburger Blätter. Jahresschrift für Heimat- und Kulturgeschichte im Bezirk Magdeburg, 1990)
Keywords: jerichow

Das Konvent zur wahren Minne: aus der Geschichte der Klosters Coldinne - Schoolmann, Heinrich (Unser Ostfriesland, 1990)
Keywords: coldinne

An Image of the Abbey Church of Prémontré under Construction - Shortell, Ellen (Gesta, 1990)
An image of construction at the abbey church of Prémontré is recorded in the stained glass from the cloister of the Premonstratensian abbey of Parc, where it serves as the focus of a scene from the life of St. Norbert. This early seventeenth-century view of the now-destroyed mother house apparently shows the medieval western façade, along with building activity in the upper parts that may date to the midthirteenth century. Thus, the window adds to our knowledge of medieval Premonstratensian buildings, and should be included in the corpus of images of medieval construction.
Keywords: prémontré

Der Apostelaltar im Ratzeburger Dom - Steffen, Uwe (Lauenburgische Heimat, 1990)
Keywords: ratzeburg

Das Prämonstratenserkloster Saint-Yved in Braine als Grablege der Grafen von Dreux: zu Stifterverhalten und Grabmalgestaltung im Frankreich des 13. Jahrhunderts - Teuscher, Andrea (Lehrstuhl I für Kunstgeschichte und Aufbaustudium Denkmalpflege an der Otto-Friedrich-Universität Bamberg, 1990)
Keywords: braine

De schenkingsoorkonde van het altaar van Denderwindeke aan de abdij van Vermand - Van De Perre, Dirk (Analecta Praemonstratensia, 1990)
Keywords: vermand

L'acte de la donation de l'autel de Denderwindeke à l'abbaye de Vermand - Van De Perre, Dirk (Analecta Praemonstratensia, 1990)
Keywords: vermand

Diplomatisch-paleografisch onderzoek van de oudste oorkonden van de Sint-Cornelius- en Cyprianusabdij van Ninove (1137-1300) - Van den Noortgate, Machteld (University of Gent, 1990)
Keywords: ninove

De oudste afbeeldingen van de St.-Michielsabdij te Antwerpen - Vander Eyken, K.J. (Bijdragen tot de geschiedenis, 1990)
Keywords: antwerp

Vier schilderijen i.v.m. de Antwerpse Sint-Michielsabdij van P. Col(l)in - Vander Eyken, K.J. (Analecta Praemonstratensia, 1990)
Keywords: antwerp

Ausgrabungen im Ostflügel von Kloster Langwaden - Vogeler, Ute (Archäologie im Rheinland, 1990)
Keywords: langwaden

An der Schwelle vom Leben zum Tod. Über ein Testament im Stift Stoppenberg 1517 - Weigel, Helmut (Vergessene Zeiten. Mittelalter im Ruhrgebiet, 1990)
Keywords: stoppenberg

Der Dom zu Havelberg - Werner, Anna Maria (Große Baudenkmäler, 1990)
Keywords: havelberg

Grundherrschaft und Bauern : eine wirtschafts- und sozialgeschichtliche Untersuchung der Grundherrschaft der Prämonstratenserabtei Rüti (ZH) im Spätmittelalter - Zangger, Alfred (University of Zürich, 1990)
Keywords: rüti